2023
DOI: 10.1109/access.2023.3234959
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Mobile RFID Authentication Protocol for Smart Logistics Targets Tracking

Abstract: Target tracking is one of the problems existing in the supply chain management. The use of radio frequency identification (RFID) in target tracking helps improve the monitoring accuracy and status visibility of the tracked target. For mobile RFID system, its three entities have to authenticate each other's identity in order to guarantee the data transmission security. The mobile RFID authentication protocol cannot achieve both high security and low complexity at the same time. For this problem, a new efficienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 25 publications
(27 reference statements)
0
1
0
Order By: Relevance
“…In recent years, ProVerif has become a popular tool [29] for protocol security verification. ProVerif particularly identifies attacks on various protocols, including Extend ProVerif [30], Bluetooth protocol design vulnerabilities [31], distance bounding protocols [32], TLS1.3 [33], on-site voting systems [34], authentication protocols for Internet of Drones environments [35], Fast Identity Online 2 [36], and the MobileRFID authentication protocol [37]. Charlie et al [38] found weaknesses in their EDHOC analysis, a key exchange proposed by the IETF's Lightweight Authenticated Key Exchange Working Group.…”
Section: B Related Workmentioning
confidence: 99%
“…In recent years, ProVerif has become a popular tool [29] for protocol security verification. ProVerif particularly identifies attacks on various protocols, including Extend ProVerif [30], Bluetooth protocol design vulnerabilities [31], distance bounding protocols [32], TLS1.3 [33], on-site voting systems [34], authentication protocols for Internet of Drones environments [35], Fast Identity Online 2 [36], and the MobileRFID authentication protocol [37]. Charlie et al [38] found weaknesses in their EDHOC analysis, a key exchange proposed by the IETF's Lightweight Authenticated Key Exchange Working Group.…”
Section: B Related Workmentioning
confidence: 99%